2011
DOI: 10.1038/jhh.2011.89
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic balance and diagnosis of pre-eclampsia: selecting the right VEGF receptor

Abstract: We read with interest the report by Rath and Tripathi 1 in which they have evaluated the levels of serum vascular endothelial growth factor (VEGF) and soluble VEFR receptor type 2 in hypertensive disorders of pregnancy. Their findings are certainly intriguing. First, they found increased VEGF levels in pre-eclampsia (PE) and eclampsia. This is contrary to what has been noted in almost all published reports that show reduced VEGF levels. [2][3][4][5] In our investigations, we have consistently found circulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In the current study, we found that IL-17 inhibition normalized sFlt-1 and partially restored circulating levels of VEGF in RUPP recipients. This is another mechanism that may contribute to the improved maternal and fetal outcomes as VEGF supplementation has been shown to ameliorate PE pathophysiology in animal models and is being considered as a potential therapeutic option for PE women (2,16,39,48,86). Together, these data indicate that the improvement in maternal blood pressure and fetal growth following IL-17RC infusion can be partially attributed to the decrease in cNK cell activation and the resultant reduction in inflammatory cytokines and increase in VEGF levels.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the current study, we found that IL-17 inhibition normalized sFlt-1 and partially restored circulating levels of VEGF in RUPP recipients. This is another mechanism that may contribute to the improved maternal and fetal outcomes as VEGF supplementation has been shown to ameliorate PE pathophysiology in animal models and is being considered as a potential therapeutic option for PE women (2,16,39,48,86). Together, these data indicate that the improvement in maternal blood pressure and fetal growth following IL-17RC infusion can be partially attributed to the decrease in cNK cell activation and the resultant reduction in inflammatory cytokines and increase in VEGF levels.…”
Section: Discussionmentioning
confidence: 85%
“…The angiogenic imbalance between s-Flt1 and VEGF has also been identified as a significant contributor to PE (48). Increased levels of sFlt-1 and decreased levels of circulating VEGF have been observed in PE women and animal models when compared with their normal pregnant counterparts (1,48,58,61).…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the comments to our article 1 by Jha et al 2 regarding the role of vascular endothelial growth factor (VEGF) and sVEGFR-2 in pre-eclampsia (PE). We agree with the observations made by Jha et al that our data (with respect to VEGF) seem only apparently dramatically opposite and we would like to provide our view to explain these differences in the results and their interpretation.…”
mentioning
confidence: 99%